GC-MS determination of steroids related to androgen biosynthesis in human hair with pentafluorophenyldimethylsilyl-trimethylsilyl derivatisation - Choi, MH; Chung, BC (ROYAL SOC CHEMISTRY, 1999)
An efficient method for the simultaneous determination of eight steroids, androstenedione, dihydrotestosterone (DHT), dehydroepiandrosterone (DHEA), testosterone, androsterone, etiocholanolone, progesterone and pregnenolone, in human hair by gas chromatography-mass spectrometry (GC-MS) using d(3)-testosterone as internal standard is described. The method involves alkaline digestion, liquid-liquid extraction and subsequent conversion to mixed pentafluorophenyldimethylsilyl-trimethylsilyl (flophemesyl-TMS) derivatives for sensitive analysis in the selected ion monitoring (SIM) mode. This method showed good overall repeatability and reproducibility of 4.88-11.24 and 3.19-9.58%, respectively. For the first time, the quantification of DHT, DHEA and pregnenolone in human hair has been achieved by GC-MS, testosterone was also quantified. The detection of four steroids in hair samples was possible in the concentration range 0.12-8.45 ng g(-1). The other four steroids, androstenedione, androsterone, etiocholanolone and progesterone, were not detected. The detection limits for SIM of the steroids varied in the range 0.02-0.5 ng g(-1), and the SIM responses were linear with correlation coefficients varying from 0.991 to 0.996 for most of the steroids studied. The concentrations of the four steroids detected were different in male and female hair samples.